Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.2214/ajr.165.6.7484578
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular adenoma.

Abstract: A 31 -year-old woman, 2 weeks postpartum, presented with right upper quadrant abdominal pain and a decrease in hematocnt from 32% to 18%. She had previously used oral contraceptives for 4 years. A non-contrast-enhanced CT scan (Fig. 1A) showed a 17-cm mass in the left lobe of the liver with hyperdense regions (45 H) consistent with internal hemomrhage. There was no free intmapenitoneal fluid. A blood-fibbed, mubtibocular, cystic mass was found at left hepatic bobectomy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In fact, radiological findings in patient with HA are often similar to those in patients with HCC. [9][10][11]…”
Section: Microscopic Examinationmentioning
confidence: 99%
“…In fact, radiological findings in patient with HA are often similar to those in patients with HCC. [9][10][11]…”
Section: Microscopic Examinationmentioning
confidence: 99%
“…Method of delivery was unreported in three pregnancies. 30,50 Results from non-pooled data One single center retrospective study reported surgical interventions and outcomes in 122 HCA patients. 3 The report included nine patients with HCA during pregnancy and observed "moderate progression" without reporting actual size.…”
Section: Outcome Of Invasive Interventions During Pregnancymentioning
confidence: 99%
“…7). HA commonly shows the common radiological findings of benign hepatocellular lesions with intra‐ and interlesion variety [8, 32]. Intratumoral hemorrhage is frequently identified, especially in larger lesions (Fig.…”
Section: Specific Radiological Findings In Each Diseasementioning
confidence: 99%
“…Intratumoral hemorrhage is frequently identified, especially in larger lesions (Fig. 7) [32]. Only a few reports have described SPIO‐enhanced MR findings of HA, but recent reports describe that HA usually shows slight uptake of SPIO, albeit lower than that of other benign lesions (Fig.…”
Section: Specific Radiological Findings In Each Diseasementioning
confidence: 99%